Portrait of the receiver - Núñez Cansado, Marian (Historia y Comunicación Social, 2014)
Over the years the concept has been modified recipient subject closely linked to changing paradigms in psychology. New advances have forced redirect both strategies as research methodologies. Evolution has not led to the invalidation of previous theories but rather the extension or supplementation of knowledge of the subject.